2018
DOI: 10.1111/sms.13319
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydration status during heat acclimation on plasma volume and performance

Abstract: The impact of hydration status was investigated during a 5‐day heat acclimation (HA) training protocol vs mild/cool control conditions on plasma volume (PV) and performance (20 km time‐trial [TT]). Sub‐elite athletes were allocated to one of two heat training groups (90 min/day): (a) dehydrated to ~2% body weight (BW) loss in heat (35°C; DEH; n = 14); (b) euhydrated heat (35°C; EUH; n = 10), where training was isothermally clamped to 38.5°C core temperature (Tc). A euhydrated mild control group (22°C; CON; n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…When considering the determinants of performance and the performance per se, HA has been demonstrated to improve maximal oxygen uptake [48,[64][65][66][67], facilitate a rightward shift of the anaerobic threshold [48,60,64,68], and most relevantly, improve exercise capacity/tolerance in the heat [46,47,60,[69][70][71][72][73][74][75][76][77], in some cases to levels comparable to temperate conditions [78]. In field-based team-sports, HA also improves intermittent exercise capacity and tolerance to the heat [79][80][81][82][83][84][85]. It is of course challenging to prove the erogenicity of HA in elite populations given it is near-impossible to assess this against an ecologically relevant control condition and thus, is something the practitioner should be mindful of when comparing responses in athletes to experimental data which is commonly collected on less well-trained individuals.…”
Section: Chronic Heat Alleviationmentioning
confidence: 99%
See 2 more Smart Citations
“…When considering the determinants of performance and the performance per se, HA has been demonstrated to improve maximal oxygen uptake [48,[64][65][66][67], facilitate a rightward shift of the anaerobic threshold [48,60,64,68], and most relevantly, improve exercise capacity/tolerance in the heat [46,47,60,[69][70][71][72][73][74][75][76][77], in some cases to levels comparable to temperate conditions [78]. In field-based team-sports, HA also improves intermittent exercise capacity and tolerance to the heat [79][80][81][82][83][84][85]. It is of course challenging to prove the erogenicity of HA in elite populations given it is near-impossible to assess this against an ecologically relevant control condition and thus, is something the practitioner should be mindful of when comparing responses in athletes to experimental data which is commonly collected on less well-trained individuals.…”
Section: Chronic Heat Alleviationmentioning
confidence: 99%
“…However, a critique of this method is that the stimulus for adaptation at the start of the intervention diminishes by the end of the intervention (especially over longer-term protocols), as the athlete enhances their ability to dissipate heat and aerobic capacity improvements are induced [26,102]. Recent data utilizing relative HR prescription [82] offer some progression in workload as cardiovascular adaptation occurs and therefore, this administration technique may offer some adaptation advantage despite reduced control over T CORE increase in comparison to other methods [103].…”
Section: What Are My Options When Implementing Heat Acclimatization/amentioning
confidence: 99%
See 1 more Smart Citation
“…The notion that permissive dehydration or restricted fluid consumption may enhance the adaptive response (e.g., plasma volume expansion) during chronic heat exposure has recently been explored. Although pathway(s) via which this might be achieved have been proposed (i.e., increased fluid regulatory, thermal, and cardiovascular strain), contention currently exists regarding the efficacy of this approach (Garrett et al, 2014;Neal et al, 2016b;Pethick et al, 2019). Additional studies are, therefore, warranted to fully elicit whether this practice is efficacious at enhancing adaptation or potentially deleterious in optimizing performance gains through compromised heat training sessions (i.e., lower workloads).…”
Section: Nutrition For Training In the Heatmentioning
confidence: 99%
“…For decades, the relationship between hydration status and performance has been closely evaluated, with hydration status being directly linked with physical performance. Many studies have reported the consequences of dehydration on physical and mental levels, highlighting humoral changes and cognitive deficits, which not only compromise normal daily activities but can negatively affect sports performance [4][5][6]. More specifically, it has been shown that the inadequate restoration of fluids during exercise compromises neuromuscular function, increases fatigue perception, reduces technical skills, affecting metabolic and autonomic nervous system parameters [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%